(untitled) (Web of Teachers: Inderscience Research, 2026)
The article examines the urgent issue of modernizing the methodology of teaching the Russian language in higher educational institutions of the Republic of Uzbekistan in the context of the digital transformation of education. The author analyzes existing approaches to teaching Russian as a foreign/non-native language, identifies the key shortcomings of the traditional model, and proposes an innovative methodology integrating digital technologies, principles of multilingual education, and intercultural communication. The study is based on an empirical analysis of the results of implementing a blended learning format in three universities in Tashkent. The effectiveness of using interactive platforms, gamification, and a project-based approach in improving students’ language competence is demonstrated. The findings reveal that innovative methods contribute to a 45% increase in students’ motivation to learn the language and a 38% improvement in pragmatic communication skills compared to traditional approaches.